IMPLEMENTASI PROGRAM ON THE JOB TRAINING (OJT) DALAM MEMPERSIAPKAN SISWA SMK MEMASUKI DUNIA KERJA - Atmoko, Irfan Dwi; Sawiji, Hery; Susilowati, Tutik (Jurnal Informasi dan Komunikasi Administrasi Perkantoran, 2012)
Abstract: This study describe to investigate : (1) the implementation of the program of On The Job Training to prepare the students of State Vocational High School 6 of Surakarta to enter the world of work; (2) the constraints encountered in the implementation the program of On The Job Training at State Vocational High School 6 of Surakarta; and (3) efforts taken to cope with the constraints in the implementation of the program of On The Job Training at State Vocational High School 6 of Surakarta. This research used the descriptive qualitative research method. The results of the research are as follows: (1) the implementation of the program of On The Job Training at State Vocational High School 6 of Surakarta has been in compliance with the prevailing procedures an can prepare its students majoring in the Office Administration particularly in the expertise competencies in terms of hard skills and soft skills to enter the world of work; (2) the constraints encountered in the implementation of the program are as follows: the students are not mentally ready to follow the program of On The Job Training, the advising teachers have a low frequency to visit the world of business and industry, (c) not all of the competencies can be done by the students, the theories accepted by the students in the class do not conform to the work practicum in the world of business and industry; and (3) the efforts taken to deal with the constraints are as follows: motivating the students, warning the advising teachers, implementing the rolling system at the work department, the advisors of the institutions give guidance to the students.   Keywords: implementation, the program of On The Job Training, students